Occurence and fate of triclosan and tetracycline in full-scale wastewater treatment plants - Winkler, Gunrun (Cranfield University, 2005)
Pharmaceutical residues gain importance as they are emitted in a vast array and quantity into the aquatic environment. The main source for most pharmaceuticals are the discharges of wastewater treatment plants. Within this study four WTPs were selected with different biological treatment processes, such as rotating biological contactor (RBC), trickling filter (TF), activated sludge plant (ASP) and oxidation ditch (OD). Samples were taken each possible treatment step and analysed for their content of Triclosan and Tetracycline and selected biomass and wastewater characteristics were also determined. Tetracycline could not be detected in any of the wastewater treatment plants, nor its degradation products, which might be suggested to their chelating nature with divalent cations, such as calcium and metals. Triclosan has been detected in almost every liquid sample of the wastewater treatment in concentrations up to 5,000 ngL-1 for influents and 800 ngL-1 for effluents. In principle it is problematic to compare elimination rates for different wastewater treatment plants, as their influent conditions may often show wide variations. However, loss rates for Triclosan within the four different treatment systems varied between 81% and 96%, showing the best and most consistent elimination rate for the oxidation ditch. Although Triclosan removal rates are shown to be significant high, discharges still contained substantial residual concentrations, which would therefore require further elimination steps. Triclosan amounts bound to extracellular polymeric substances seemed to adversely a.ect discharge values. This is most likely due to the desorption processes occurring in the secondary clarifier. The correlation between liquid and biomass characteristics are weak to moderate, probably due to influences of uncontrolled factors associated with the operation of a full scale treatment work system from which all the samples were obtained. Among all of the determined liquid and biomass characteristics temperature, pH and lipid content showed themselves to be the most significant, with regards to the overall removal of Triclosan. Furthermore, few parameters, such as chemical oxyen demand or specific oxygen demand* within influent or oxidation ditch samples seemed to have impact on either Triclosan concentration of the bulk phase of the oxidation ditch or the Triclosan uptake within the EPS.